Interaction Mechanism between Teachers’ Emotional Intelligence Experiences and Conflict Management Styles from the Perspective of Educational Phenomenology: An Empirical Qualitative Study - Fang, Chao; Sarao, Gracia (Journal of Qualitative Research in Education, 2025)
This study adopts an educational phenomenological perspective. It explores the emotional intelligence experiences of 12 secondary school teachers in conflict management through semi-structured in-depth interviews. The research examines how these experiences interact with management styles. The findings reveal five core dimensions of teacher emotional intelligence experiences. First, bodily awareness forms the embodied foundation of emotional intelligence. Teachers identify emotions through physiological signals such as "tightness in the chest" and "trembling hands." These signals activate regulation mechanisms. Second, the relational self is dynamically constructed during conflicts. Teachers negotiate among multiple identities including "authority figure-caregiver" and "evaluator-supporter." This positioning directly influences the choice of management styles. Third, situational sensitivity serves as the core of practical wisdom. Teachers integrate five-dimensional cues from interpersonal dynamics, events, culture, time, and space. They make "here-and-now" judgments based on these cues. Fourth, emotional regulation ability develops through four stages: suppression, disguise, integration, and naturalization. Reflective practice drives stage transitions and reduces emotional exhaustion. Fifth, the meaning-making framework evolves from "conflict as threat" to "conflict as opportunity." This evolution marks a qualitative transformation in professional maturity. The study reveals that the interaction between emotional intelligence experiences and conflict management styles is not a linear causal relationship. Instead, it forms a cyclical interactive process. This process operates through mediating mechanisms such as identity negotiation, situational judgment, and meaning construction. The research provides theoretical insights grounded in lived experiences for teacher education. It calls for moving beyond the instrumental rationality of skills training. The study emphasizes the central role of reflective practice and professional identity reconstruction in teacher emotional intelligence development.